The impact of obesity on upper airway anatomy as assessed by magnetic resonance imaging and obstructive sleep apnea endotypic traits - Nokes, Brandon; Schueler, Aaron; Darquenne, Chantal; Schmickl, Cristopher N.; Wojeck, Brian S.; Moore, Stacie; Deyoung, Pamela; McGinnis, Lana; Theilmann, Rebecca J.; Gruenberg, Eli; Grunvald, Eduardo; Holloway, Breanna M.; et al. (Frontiers in Physiology, 2025)
IntroductionObesity is an important risk factor for obstructive sleep apnea (OSA) development. Likewise, obesity management is an important component of OSA treatment. We sought to evaluate the OSA endotypes as well as upper airway anatomy, using magnetic resonance imaging (MRI) in patients referred from a bariatric surgery clinic.MethodsThe SLIM-OSA trial (NCT04793334; IRB#191948) seeks to elucidate the mechanisms for why weight loss improves OSA in some but not all individuals. Participants underwent baseline research polysomnography. Six months following sleeve gastrectomy for those who underwent surgery, polysomnography was repeated. A subset of these individuals also completed upper airway magnetic resonance imaging (MRI). We evaluated relationships between upper airway anatomy and endotypic traits.ResultsOf 55 individuals undergoing baseline studies, 22 completed upper airway MRI and polysomnography at baseline, with 5 individuals returning for MRI and polysomnography after sleeve gastrectomy. The study population was 86.4% female, with a mean age of 41.7 (11) years and median AHI of 11/h [IQR 2, 33]. Upper airway length was strongly associated with apnea hypopnea index (AHI), hypoxic burden, and ventilatory burden; somewhat surprisingly, tongue fat percentage was not associated with AHI.ConclusionThe relationship between obesity and OSA is complex and likely evolves through multiple mechanistic avenues. These findings may help inform future mechanistic studies aimed at understanding the heterogeneous impact of weight loss on OSA outcomes.